Comparative Efficacy of Phonophoresis with Naproxen and Ultrasound Therapy on Pain and Grip Strength in Lateral Epicondylitis - Anwar; PT , Dr. Rabia; Shahzad , Aamir; Khalid , Hurab; Bajwa , Areej Akmal; Saif , Zulaikha; Iftikhar, Fatima; Hussain, Mir Arif (American Journal of Health, Medicine and Nursing Practice, 2023)
Purpose: Lateral epicondylitis, also referred to as "tennis elbow," is a painful condition resulting from the inflammation of tendons situated along the exterior of the elbow, which serve to connect the muscles of the forearm. The primary aim of this study was to assess and compare the therapeutic effects of phonophoresis with naproxen versus ultrasound therapy in managing pain levels and enhancing grip strength in individuals suffering from lateral epicondylitis Methodology: This quasi-experimental study comprised a sample size of 42 participants, selected through convenient sampling methods over duration of 8 months. The inclusion criteria stipulated that individuals of both genders, aged between 31 and 50 years, experiencing chronic pain in the elbow and forearm for a period exceeding 3 months, and exhibiting a positive response to the Mill's test, were eligible for participation. The participants were divided into two groups, each consisting of 21 subjects. Out of the 42 patients, 21 were assigned to Group 1, which received baseline therapy along with Phonophoresis utilizing naproxen, while the remaining 21 were allocated to Group 2, which received baseline therapy in conjunction with therapeutic ultrasound. Both groups had received baseline treatment of stretching and strengthening exercises. Four sessions of interventions were given per week, for four weeks. Intensity of pain was assessed by Visual analogue scale (VAS) before and after the treatment of 4 week and grip strength was measured by handheld dynamometer. There were two drop outs in group 1 and three in group 2. The collected data was analyzed and interpreted by using SPSS software of version 24.0 Findings: Among the 42 participants (with 21 in each group), 67% of patients in Group 1 were male, while 33% were female. In Group 2, 42.9% were male, and 57.1% were female. For Group 1, the median grip strength value before treatment was 60.00, which significantly decreased to 20.00 after treatment. Similarly, in Group 2, the median grip strength value before treatment was 70.00, and it also decreased significantly to 20.00 after treatment. The pre-treatment mean grip strength in Group 1 was 36.46±8.82, which increased to 50.59±11.33 after 4 weeks of treatment. In Group 2, the pre-treatment mean grip strength was 31.12±4.87, and it increased to 52.02±9.70 after treatment. A statistically significant difference was observed in both groups when comparing pre- and post-treatment grip strength values (p<0.001). However, the between-group analysis comparing Group 1 and Group 2 showed no statistically significant difference (p>0.05).. Recommendations: Based on the study's findings, both phonophoresis with naproxen and therapeutic ultrasound are effective in managing pain and improving grip strength for lateral epicondylitis patients. Clinicians should consider incorporating these treatments into their therapeutic regimens for such patients. Future research should consider larger sample sizes and explore other therapeutic modalities to ascertain the most effective treatment option. Additionally, understanding the long-term effects and sustainability of the noted improvements would benefit clinical practice and enhance patient care outcomes.